US and the Arctic Region in the Era of Climate Change: A Brief Analysis of the Evolution of US Arctic Foreign Policy Since 2000s - Emirhan Altunkaya (İstanbul Gelişim Üniversitesi Sosyal Bilimler Dergisi, 2019)
The objective of this paper is to provide an updated analysis of the United States (US) foreign policy towards the Arctic Region since the 2000s when the political, economic and security-related significance of the region is growing due to the impacts of climate change. It aims to analyze the development of the US foreign policy towards the region under three respective (Bush, Obama, Trump) administrations and to reveal differing priorities of three respective administrations. Therefore the research question of the following paper is; "What constitutes the main objectives of the US Arctic foreign policy in a climate-changed era and how has it evolved since the 2000s under three administrations?" The method used is a qualitative analysis of official policy and security documents, administration’s engagement and positioning related to the region, but also various reports published by think-tanks and experts to evaluate the US Arctic foreign policy in the face of emerging challenges and opportunities.